PENGARUH BEBAN PAJAK, PERENCANAAN PAJAK DAN TAX HAVEN TERHADAP TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Kholifatun, Siti; Mutiara Pabulo, Azfa (ITB AAS Indonesia Surakarta, 2025)
This study was conducted to determine the effect of tax burden, tax planning, and tax havens on transfer pricing in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2022-2024. The population in this study was all food and beverage manufacturing companies listed on the Indonesia Stock Exchange in the 2022-2024 period. The data analysis technique used SPSS. The results of the study indicate that tax burden has an effect on transfer pricing in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in the 2022-2024 period. Tax planning has no effect on transfer pricing in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in the 2022-2024 period. Tax havens have no effect on transfer pricing in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in the 2022-2024 period.